ANALISIS KUALITAS ES KRIM DENGAN PENAMBAHAN BUAH SENDUDUK - Yolanda Intan Sari (Pasundan Food Technology Journal (PFTJ), 2023)
The function of this research is to analyze the quality of ice cream that is fruit senduduk as much 40gr, 80gr, 120gr to quality color, aroma, texture, and flavor. This type of research is purely experiment using the method of complete random design using three repetitions with 25 people semi trained panelists at the workshop Layout Boga Majors IKK, FPP, UNP in may 2018. Instrument used is the question form which is then analyzed by organoleptic testing beneath it through. to test the hypothesis using statistical test of ANAVA then proceeded with the test results of the study showed there was significant influence between 40gr, 80gr, 120gr on quality ice cream that is on the quality of the color and flavor of ice cream. While the aroma of milk, soft texture, sweetness, flavor, milk has no effect. The best percentage result is present on the addition of fruit senduduk on ice cream as much as 80 Gr. to quality color